Acute myocardial infarction in pregnancy: spasm caused by hyperthyroidism? - Wang, LingQing (J Int Med Res, 2019)
We present a 26-year-old woman with ST-segment elevation myocardial infarction in the 14th week of pregnancy. Coronary angiography revealed no abnormalities in the coronary arteries. She had no history of coronary risk factors such as smoking, diabetes mellitus, hypertension, or dyslipidemia. Although we do not have direct evidence of coronary spasm in this patient, several factors suggest that coronary spasm is the most likely cause of myocardial infarction. We suspect that hyperthyroidism may have played an important role in coronary spasm in this patient. Early use of coronary angiography is helpful to identify the types of coronary artery lesions.